Benefits of Liver Volume and Serum Zinc Level Assessment for the Screening of Covert Hepatic Encephalopathy in Patients with Child–Pugh Class A Cirrhosis - Masanori Fukushima; Hisamitsu Miyaaki; Ryu Sasaki; Yasuhiko Nakao; Masafumi Haraguchi; Kosuke Takahashi; Eisuke Ozawa; Satoshi Miuma; Kazuhiko Nakao (Diagnostics)
Background/Objectives: Covert hepatic encephalopathy (CHE) is associated with decreased quality of life. Detection of Child–Pugh class A is necessary for its early diagnosis. This study aimed to establish a simple diagnostic method of CHE in patients with Child–Pugh class A. Methods: One hundred patients with liver cirrhosis without overt hepatic encephalopathy and sixty-eight with liver cirrhosis and Child–Pugh class A who visited our institution were enrolled. CHE was diagnosed using number connection test B in the neuropsychiatric test (NPT). Clinical data were compared. Results: The liver volume/body surface area ratio (LV/BSA) was associated with CHE in patients with all-cause and Child–Pugh class A liver cirrhosis. Multiple logistic regression analysis revealed that low LV/BSA and low serum zinc (Zn) levels were significantly associated with CHE in Child–Pugh class A liver cirrhosis. The best cutoff values in the receiver operating characteristic curve analysis showed that the complication rate of CHE was 54.8% in patients with LV/BSA < 620 mL/m2, which was 2.9 times higher than that in patients with larger liver volume. Referring to the cutoff values for LV/BSA and Zn (<70 µg/dL), in cases with LV/BSA < 620 mL/m2 and Zn < 70 µg/dL, 64.2% had CHE, whereas in cases with LV/BSA ≥ 620 mL/m2 and Zn ≥ 70 µg/dL, 94.5% did not have CHE. Conclusions: Liver volume can be used as a risk assessment tool for CHE. LV/BSA and serum Zn levels are considered effective diagnostic tools for CHE, serving as alternatives to NPT in patients with Child–Pugh class A liver cirrhosis.